Seatbelt‐induced extrathoracic lung herniation - Kitridis, Dimitrios (Clin Case Rep, 2020)
Traumatic lung herniation is an uncommon complication of blunt chest trauma due to seatbelt injury. High index of suspicion, adherence to ATLS guidelines, and cooperation between different surgical specialties for the prompt stabilization of flail chest and primary or prosthetic closure of the defect may ensure a favorable outcome.